Clinical Recommendations of the Northwest Society for Enteral and Parenteral Nutrition, Interregional Association for Emergency Surgery, Russian Gastroenterological Association, Union of Rehabilitation Therapists of Russia and Russian Transplantation Society on Diagnosis and Treatment of Short Bowel Syndrome-Associated Intestinal Failure in Adults - Yu. V. Averyanova; E. M. Batyrshin; A. E. Demko; G. E. Ivanova; V. T. Ivashkin; L. N. Kostyuchenko; A. V. Lapitsky; I. N. Leiderman; V. M. Luft; I. V. Maev; I. G. Nikitin; M. S. Novruzbekov; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. Current clinical recommendations address the epidemiology, causes, clinical manifestations and pathogenesis of possible immediate and long-term complications, as well as the problematic issues related to treatment and rehabilitation of adult short bowel syndrome patients.Key points. Short bowel syndrome (SBS) is a symptom complex of impaired digestion caused by the reduction of small intestine absorptive surface and manifested by intestinal failure (IF) of various severity (maldigestion and malabsorption) developing into malnutrition and systemic somatogenic disorders. The vital strategic aspects of its treatment are the personalisation of liquid, macro- and micronutrients consumption as well as avoidance of intestinal failure- and parenteral nutrition-associated complications. Various nutritional support regimes and the indications for infusion therapy and maintenance parenteral nutrition are considered in this patient category, also in outpatient settings. To mitigate the dependence on intravenous fluid- and nutrient administration and attain enteral autonomy in SBS-IF patients, the use of recombinant glucagon-like peptide-2 (GLP-2) is justified as exerting a pronounced trophic effect on the epithelial regenerative potential as well as structural and functional adaptation of intestinal mucosa. The SBS-IF patients prescribed with home parenteral nutrition and/or their caregivers should be trained in a special programme that covers the catheter care, preparation of infusion solutions and nutrient mixture container, infusion pump operation as well as the prevention, recognition and management of complications. The main referral indications for small bowel transplantation (SBT) are: fast-progressing cholestatic liver disease-complicated irreversible intestinal failure; thrombosis of two or more central venous conduits used for parenteral nutrition; recurrent catheter-associated bloodstream infection.Conclusion. Current recommendations on diagnosis and treatment as well as the developed criteria of medical aid quality assessment are applicable at different levels of healthcare.